From Book to Playlist: How Open-Access Audio Archives are Renewing the Poetry Collection - Abigail Lang (Sillages Critiques)
Open-access audio archives are changing the ways we consume and conceive of poetry. This article considers exactly how they renew our sense of the poetry collection. While books provide authoritative collections assembled by a poet or an editor, open-access audio repositories with an archival concern preserve entire poetry readings in which poems are read in a different order than in print. Given the ability of poems to take up new meaning according to context – a characteristic identified by Neil Fraistat as “the Petrarchan paradigm” –, I argue that such “sets” constitute hermeneutic objects in themselves and in relation to print collections. To test this hypothesis, I turn to Louis Zukofsky, a poet known for the careful structuring of his books and his radical care for sound. Listening closely to two 1972 readings and examining a reading program for a 1941 reading at the YMHA preserved in the Zukofsky archives, I establish that such sources offer valuable insights into the work, expose a series of criteria used by poets to compose their readings, show how a poet can repurpose old poems in renewed contextures, and ultimately observe that approaching Zukofsky through his audiotexts tilts his work decisively toward song. Moreover, Zukofsky’s Fall 1972 readings foreground the curatorial role played by his wife, Celia Zukofsky. By setting to music her selections from her husband’s work, she offers two artistically complex textual realizations of a game-changing affordance of sound-recording technologies since the 1963 invention of the audio cassette – i.e. the possibility to anthologize on the receiving end. In large online repositories of recorded poetry, the playlist has become an established genre with a curatorial function, offering guided tours by artists or scholars. Tapping the widely shared desire to collect “favorites,” share them with others, and prompt them to come up with their own list in response, the playlist undeniably holds great critical, creative, and pedagogical potential.